The PISS (Prevention, Integrative, Solidarity and Stimulus) Model in Handling COVID-19 in Pekanbaru City - Wan Asrida; Auradian Marta; Wazni Wazni (Ridwan Institute, 2023)
The COVID-19 outbreak has had a very broad impact on the social, economic and health sectors. Therefore, an effective policy model is urgently needed in handling COVID-19. This study seeks to explain how the policy model is in handling COVID-19 in Pekanbaru City. The research method used is a qualitative approach by collecting data through interviews and document searches. The results of this research indicate that there are four basic things in the policy model for handling COVID-19 in Pekanbaru, namely Prevention, Integration, Solidarity and Stimulus. The four approaches in the policy model for handling COVID-19 are carried out simultaneously, not only useful in minimizing the spread of COVID-19 but also useful in dealing with the impact of COVID-19.